Natural fluorescent red colorants produced by Talaromyces amestolkiae as promising coloring agents for custom-made latex gloves - Mussagy, Cassamo U.; Oshiro, Ariane A. [UNESP]; Lima, Caio A. [UNESP]; Amantino, Camila F. [UNESP]; Primo, Fernando L. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP]; Herculano, Rondinelli D. [UNESP] (Elsevier, 2023)
Synthetic-based colorants have been extensively used in several industries, viz., cosmeceutical, feed, pharmaceuticals, food and textile. However, the growing awareness of potential teratogenicity, carcinogenicity and environmental concerns of certain synthetic colorants have expressed several limitations regarding their use in some products. These limitations, justifies the motivation to look for eco-friendly alternatives (cf., natural colorants) to be used as coloring agents for industrial applications. The filamentous fungi Talaromyces amestolkiae appeared as a promising source of natural fluorescent red colorant (NFRC) for the development of custom-made latex gloves. In this study, some basic colorant properties, including 3D-fluorescence and CIELAB color characteristics were first investigated systematically before their incorporation in natural rubber latex (NRL) films. The NFRC-NRL films properties were evaluated by physicochemical tests and toxicity through cell viability using 3T3 fibroblasts, wherein eluate of NFRC-NRL films (2.28 AU) revealed viability >70 % (exposing the biocompatibility). Regardless of the strategy proposed, it is shown as a proof-of-concept the potential application of NFRC in the NRL matrix as a biocompatible alternative to produce sustainable commercial colored custom-made latex gloves.
Keywords: Filamentous fungi; Gloves; Natural rubber latex; Polyketides colorants